1991
DOI: 10.1159/000125932
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Enhances the Speed of the Recovery of the Hypothalamo-Pituitary-Adrenocortical Axis after Chronic Prednisolone Administration in the Rat

Abstract: Chronic administration of corticosteroids results in a suppression of the hypothalamo-pituitary-adrenocortical (HPA) axis. The time course of the recovery of the HPA axis depends on the dose and duration of corticosteroid administration. We investigated the recovery of the HPA axis after 14 days of prednisolone administration to rats at a dose of 2.0 mg/rat/day via the drinking water (188 µmol/l). The in vitro corticosterone production by dispersed adrenal cells in response to increasing concentrations of ACTH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The FST is primarily associated with the dopaminergic and serotonergic systems, while the TST is associated with the adrenergic system (Martin and Brown 2009). Our findings that the stress-induced increase in plasma corticosterone and ACTH concentrations are suppressed by the administration of clomipramine are in line with other authors' results (Aulakh et al 1993;Martin and Brown 2009;Marzouk et al 1991). Placebo analgesia also decreased the stress-induced corticosterone and ACTH concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…The FST is primarily associated with the dopaminergic and serotonergic systems, while the TST is associated with the adrenergic system (Martin and Brown 2009). Our findings that the stress-induced increase in plasma corticosterone and ACTH concentrations are suppressed by the administration of clomipramine are in line with other authors' results (Aulakh et al 1993;Martin and Brown 2009;Marzouk et al 1991). Placebo analgesia also decreased the stress-induced corticosterone and ACTH concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…[54] have demonstrated that rats implanted to moderately in crease basal a.m. corticosterone show normal ACTH but depressed plasma corticosterone responses to stress in the p.m. In addition, dispersed adrenal cells, from rats treated with corticosteroids in vivo, have been shown to secrete less corticosterone in response to ACTH challenge [55]. It must be noted however that animals bom by C section with no added anoxia (0-min anoxia group) showed no change in basal corticosterone secretion, but still hyposecreted corticosterone in response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…A similar procedure was followed to measure plasma free T3 (FT-,). Corticosterone was esti¬ mated by RIA (Marzouk et al 1991). Detection limits were 02 µg RP-2 TSH/1, 2 nmol T4/l, 01 nmol T3/l and 1 nmol corticosterone/1.…”
Section: Hormone Determinationsmentioning
confidence: 99%